Airway Pressure Release Ventilation With Time-Controlled Adaptive Ventilation (TCAV™) in COVID-19: A Community Hospital’s Experience - Rola, Philippe; Daxon, Benjamin (Frontiers in Physiology, 2022)
Santa Cabrini Ospedale, a community hospital in Montreal, Canada, used the airway pressure release ventilation following a time-controlled adaptive ventilation (APRV-TCAV™) approach for several patients in the first wave of the coronavirus disease 2019 (COVID-19) outbreak in the spring of 2021. Based on favorable patient responses, it became the primary mode of invasive mechanical ventilation—from initiation through extubation—during the second and third waves of COVID-19. In this article, we describe our success with APRV-TCAV™ over more conventional modes and protocols and look at three cases that aptly demonstrate our experience. We then outline several risks with our approach and the lessons learned from our experience. While we generally saw improvement in patients’ clinical course with APRV-TCAV™, there are inherent risks with this approach that others must prepare for if they attempt to implement it in their practice.